1990
DOI: 10.1002/ajh.2830350103
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of bone marrow erythropoietic stem cells (CFU‐E and BFU‐E) to recombinant human erythropoietin (rh‐Ep) in vitro in aplastic anemia and myelodysplastic syndrome

Abstract: Responsiveness of bone marrow erythropoietic stem cells (CFU-E and BFU-E) to recombinant human erythropoietin (rh-Ep) was examined in vitro in 23 patients with aplastic anemia and 14 with myelodysplastic syndrome (MDS) to investigate the clinical use of rh-Ep for these diseases. Bone marrow mononuclear cells were cultured by methylcellulose methods for CFU-E and BFU-E assays. In normals, the CFU-E numbers reached a plateau of increase at Ep doses of almost 2-5 units, and no further increase was observed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Here again differences in composition of study populations and in culture techniques might account for 63 the conflicting results obtained. Actually, a significant in crease in the number of erythroid progenitors in response to high levels of rhEPO has been observed in vitro in a sub set of MDS patients [27]. These findings confirm that at least in some MDS patients EPO-sensitive progenitor cells are present and arc able to respond to pharmacolog ical doses of rhEPO.…”
Section: Discussionsupporting
confidence: 72%
“…Here again differences in composition of study populations and in culture techniques might account for 63 the conflicting results obtained. Actually, a significant in crease in the number of erythroid progenitors in response to high levels of rhEPO has been observed in vitro in a sub set of MDS patients [27]. These findings confirm that at least in some MDS patients EPO-sensitive progenitor cells are present and arc able to respond to pharmacolog ical doses of rhEPO.…”
Section: Discussionsupporting
confidence: 72%
“…Several in vitro studies have shown that erythroid progenitors in vitro do not expand in response to epo or epo plus MGF stimulation. [2][3][4][5][6][7][8] Also the in vivo treatment of MDS patients with rhEPO is of limited benefit. [25][26][27] However, in spite of the limited in vitro proliferative capacity of the erythroid progenitor cell, a normal or increased number of normoblasts are observed in the bone marrow suggesting that in vivo the differentiation pathway is not totally blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have shown that BFU-E and CFU-E do not expand in response to erythropoietin (Epo) or Epo plus mast cell growth factor (MGF). [2][3][4][5][6][7][8] Moreover a differentiation block is observed at the level of early erythroid progenitor cell which is frequently associated with the aberrant expression of Evi-1. 9 The Evi-1 gene encodes a zinc finger protein that functions as transcription factor.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro culture studies using unsorted bone marrow mononuclear cells from patients with MDS found that erythroid progenitors such as erythroid burst-forming units (BFU-Es) and erythroid colony-forming units (CFU-Es) did not expand correctly in response to erythropoietin (Epo) alone or to a mixture of Epo, stem cell factor (SCF), and interleukin-3 (IL-3). [1][2][3] In most patients with MDS, BFU-Es also failed to emerge from sorted CD34 ϩ CD36 Ϫ cells. 4 Proliferation of CD34 ϩ and CD34 ϩ CD38 Ϫ progenitors in serum-free medium was impaired, despite optimal concentrations of SCF, flt-3 ligand, thrombopoietin, IL-3, granulocyte colony-stimulating factor, granulocytemacrophage colony-stimulating factor (GM-CSF), and Epo.…”
Section: Introductionmentioning
confidence: 99%